Evaluation and selection of curtain wall systems for medium‐high rise building construction. Issue 4 (2014) - Abdul‐Mohsen Al‐Hammad; Mohammad A. Hassanain; Mohammed N. Juaim
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present a systematic approach for the evaluation and selection of curtain wall systems for medium‐high rise building construction. Design/methodology/approach – The authors have identified the different types of curtain wall systems that are commonly used in the building construction industry in Saudi Arabia; examined the various performance as well as financial and non‐financial criteria affecting the evaluation and selection of these systems; and subjected the identified different types of curtain wall systems to several filtering processes, namely feasibility ranking, evaluation by comparison and weighted evaluation to facilitate making a decision on the most suitable system to select. Findings – The analysis of the collected data indicated that the precast concrete curtain wall system is considered to be the first choice. The second choice is the prefabricated brick panel curtain wall system. Originality/value – Curtain walls are the most recognized elements of contemporary structures today. There exists ample variety of materials and designs that could be utilized for the development of these building elements. This paper is of practical value to project owners, architects and design professionals endeavoring on the process of selecting and specifying curtain wall systems in their projects. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors thank the King Fahd University of Petroleum and Minerals for the support and facilities that made this research possible. </ack>